Way down we go : using bottom trawling to survey benthic debris in Icelandic waters - Blache, Mathis, 1996- (2021)
Verkefnið er lokað til 28.05.2022. In 2011, the UN Environment Programme defined marine litter, with a particular emphasis on plastic debris, as a major global concern and threat to life in the oceans worldwide. Over the last few years, the number of studies reporting accumulations of marine debris on the seafloor has increased substantially, suggesting that the benthic environment could be a major sink for items discarded both at sea and on land. However, only a handful of studies have investigated marine litter distribution in the Arctic environment. They showed that the presence of debris is widespread across all habitat types, although the abundance varies strongly depending on the type of debris, the locations and the processes acting on them. Therefore, our understanding of the sources, path and fate of marine debris in the Arctic remains limited. This study provides the first large scale benthic debris survey within the Icelandic EEZ and tries to assess the potential to use bottom trawling as a sampling method for marine litter. Data were collected using benthic trawling during the annual standardized fish stock monitoring conducted by Hafrannsóknastofnun in 2019 and 2020. Results showed that benthic debris is ubiquitous on the Icelandic continental shelf, with most items made of plastic and originating from the fishing industry. Background benthic litter abundance found ranged from 0.35 ± 0.04 (SEM) to 86.83 ± 25.06 (SEM) items/km² among surveys. However, the sampling methods were demonstrated to be flawed and to underestimate the amount of debris, and differences in the fishing gear design were shown to strongly influence the results. Ultimately, spatial variations were detected and potential paths for transport of marine debris in Icelandic waters were discussed. Árið 2011 var rusl í hafinu skilgreint, af umhverfisáætlun Sameinuðu þjóðanna (UNEP), sem ein helsta ógn við lífríki hafsins á heimsvísu, og stöfuðu helstu áhyggjur af plasti. Undanfarin ár hafa birst sífellt fleiri niðurstöður rannsókna ...